Innovation Design Creating Value for People, Organizations and Society - den Ouden, Elke.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2012)
Innovation Design presents an approach to designing shared value for businesses, non-profit organizations, end-users and society. The societal and economic challenges we are currently facing – such as the aging population, energy scarcity and environmental issues – are not just threats but are also great opportunities for organizations. Innovation Design shows how organizations can contribute to the process of generating value for society by finding true solutions to these challenges. And at the same time it describes how they can capture value for themselves in business ecosystems that care for both people and planet. This book covers: ·         Creating meaningful innovations that improve quality of life, engage users and provide value for organizations and other stakeholders; ·         Guiding the creation of shared value throughout the innovation process, with a practical and integrative approach towards value that connects ideas from economics, psychology, sociology and ecology; ·         Designing new business models and business ecosystems to deliver sustainable benefits for all the involved parties and stakeholders, addressing both tangible and intangible value. Innovation Design gives numerous examples of projects and innovations to illustrate some of the challenges and solutions you may encounter in your journey of designing meaningful innovations and creating shared value. It also offers practical methods and tools that can be applied directly in your own projects. And in a fast-changing world, it provides a context, a framework and the inspiration to create value at every level: for people, for organizations and for the society in which we live.
1. Innovating in the Age of Transformation -- 2. Creating Value with New Value Propositions -- 3. Designing New Business Models and Ecosystems.
Keywords: Engineering economics; Engineering economy; Management; Professional education; Vocational education; Organization; Planning; Entrepreneurship; Engineering Economics, Organization, Logistics, Marketing; Management; Professional & Vocational Education; Organization; Entrepreneurship